Enhancing C─C Bond Cleavage of Glycerol Electrooxidation Through Spin‐Selective Electron Donation in Pd–PdS2–Cox Heterostructural Nanosheets - Liu, Pei; Ma, Hao; Qin, Yuchen; Li, Junjun; Li, Fengwang; Ye, Jinyu; Guo, Qiudi; Su, Ning; Gao, Chao; Xie, Lixia; Sheng, Xia; Zhao, Shiju; et al. (Angewandte Chemie International Edition, 2025)
As a 4d transition metal, the spin state of Pd is extremely difficult to directly regulate for the optimized d orbital states owing to the strong spin‐orbit coupling effect and further extended d orbital. Herein, we devise a “spin‐selective electron donation” strategy to tune specific d orbital electrons of Pd inspired by the Dewar−Chatt−Duncanson model theory. Co−S−Pd bridges with different spin‐states of CoIII have been constructed in a series of Pd–PdS2–Cox HNSs with tunable Co content. Experiments and theoretical calculations indicate that low‐spin CoIII (t2g6eg0) with fully occupied t2g orbitals and empty dz2$d_{{z^2}}$ orbitals can accurately alter the dz2$d_{{z^2}}$ electron of Pd by σ‐donation via the Co−S−Pd bridge. In contrast, the unfilled dxy orbital of high‐spin CoIII (t2g5eg1) is essential for controlling the dxy electron of Pd via π‐donation. Benefiting from dz2$d_{{z^2}}$ state optimization by σ‐donation, Pd–PdS2–Co4.0 delivers superior performance toward various bio‐alcohols (ethanol, ethylene glycol, and glycerol) with enhanced C─C bond cleavage. Furthermore, coupling the glycerol oxidation reaction with the CO2 reduction reaction (GOR||CO2RR), the electricity consumption of GOR||CO2RR drops 46.4% compared to the state‐of‐art system (OER||CO2RR). Moreover, anodic Faraday efficiency (FE) of formic acid can be attainable at more than 90% at low voltage regions. The “spin‐selective electron donation” strategy effectively modulates the electronic states of Pd's d orbitals (dz2${d_{{z^2}}}$ and dxy) through distinct pathway: σ‐donation from low‐spin CoIII (t2g6eg0) and π‐donation from high‐spin CoIII (t2g5eg1).